(3GdSeW GdZGdi GdKef aj CNHGQ Gdedhc ef GdZR HGdjefs - (3eMeO Hf MGJe GdjGej GdjeGfj GdgeOGfj GdjGej , GdCejQ HOQ GdOjf,J (B702 (3g` s
(3ChdgG (B:s
(3hHYO , adeG cGfJ GdCNHGQ hGdSjQ eeG JWdY GdfahS GdfajSI EdjgG (B,(3de jcf CMO UQa eeJg Edi CNHGQ GdZR HGdjef CMHHJ Cf Cdhf GdSGHb Edi Pdc s
(3BNQgG (B:s
(3Ke GSJYUeJ HebGe ehdGfG GdebGe GdCYXe GdegOi , NdO Gddg edcg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B75 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B167s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B323 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B555 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B234 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs